Carbon nanotube / silicon three-dimensional composite material and preparation method and application thereof
By performing surface chemical state regulation and vapor deposition processes on the surface of spherical silicon powder, combined with the composite activator system and multi-stage heat treatment process, the orderly growth of carbon nanotubes is achieved, solving the problems of unstable growth and random orientation in the prior art, and significantly improving the structural stability and electrochemical properties of the composite material.
Patent Information
- Application Number
- CN202510084467.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the preparation method of silicon/carbon nanotube composite material is difficult to achieve the controllable growth of carbon nanotubes on the surface of silicon powder, especially the precise construction of catalytic centers and the regulation of growth orientation, resulting in low interface bonding strength and unstable structural structure.
Through surface chemical state regulation and vapor deposition processes, a three-dimensional structural silicon carbon anode material is constructed on the surface of spherical silicon powder, and the orderly growth of carbon nanotubes is achieved by using a composite activator system and a multi-stage heat treatment process to form a unique three-dimensional network structure.
The controlled growth of carbon nanotubes on the surface of silicon powder is achieved, the interface bonding strength and structural stability are improved, and the electrochemical performance and cyclic stability of composite materials are significantly improved.
Smart Images

Figure CN119774617A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon nanotube / silicon three-dimensional composite material and a preparation method and application thereof, belonging to the technical field of materials, in particular to the technical field of nanocomposite materials. Background Art
[0002] With the rapid development of the new energy revolution and electronic information technology, the research and development of high-performance electrochemical energy storage devices has become the focus of global scientific and technological innovation. Lithium-ion batteries have shown great application potential in portable electronic devices, electric vehicles, and large-scale energy storage due to their excellent energy density, environmental compatibility, and service life. However, the theoretical capacity of traditional graphite anode materials is only 372mAh / g, which can no longer meet the urgent needs of high-energy density energy storage systems. In this context, silicon-based anode materials with ultra-high theoretical capacity (4200mAh / g) have attracted widespread attention from academia and industry.
[0003] The significant volume effect (>300%) of silicon-based negative electrode materials during the charge and discharge process leads to electrode structure collapse and electrical contact loss. This intrinsic defect seriously restricts its practical application. At present, the construction of nanostructures and carbon-based composites has been proven to be an effective strategy for regulating the interface stability and electrochemical kinetics of silicon-based electrodes. Among them, carbon nanotubes have outstanding advantages in constructing high-performance silicon-based composite negative electrode materials due to their unique one-dimensional tubular structure, excellent mechanical properties (Young's modulus ~1TPa), electrical conductivity (104-106S / cm) and chemical stability.
[0004] In the prior art, the preparation methods of silicon / carbon nanotube composite materials mainly include the following categories:
[0005] (1) The mechanical composite method based on ball milling is simple in process but has low interface bonding strength and cannot achieve nanoscale structural control;
[0006] (2) Traditional chemical vapor deposition requires complex process equipment and strict control of growth conditions, and there is a problem that the orientation and degree of graphitization of carbon nanotubes are difficult to control;
[0007] (3) Solution methods, such as electrostatic assembly and covalent bond grafting, often introduce a large amount of interface regulators, which not only increases the complexity of the process, but also seriously affects the conductive network of the material and the interface electron transport dynamics;
[0008] (4) Although the in-situ growth method has the advantage of close interface bonding, the existing technology generally has problems such as uneven catalyst distribution and random growth orientation, making it difficult to construct a three-dimensional conductive network with optimized electron / ion transport channels.
[0009] Therefore, how to achieve the controllable growth of carbon nanotubes on the surface of silicon powder, especially the precise construction of the catalytic center and the regulation of the growth orientation, is a key scientific problem that needs to be solved in this field. This requires not only a deep understanding of the microscopic mechanism of interfacial catalysis and carbon nanotube growth, but also the coordinated regulation of multi-scale structures at the process level. In summary, the development of a method for preparing silicon / carbon nanotube composites that combines scientific principle innovation and engineering practice value is of great practical significance for promoting the industrialization of high-performance lithium-ion battery negative electrode materials. Summary of the invention
[0010] In order to solve the above shortcomings and deficiencies, the purpose of the present invention is to provide a carbon nanotube / silicon three-dimensional composite material and its preparation method and application. The present invention uses surface chemical state regulation and vapor deposition process to directionally construct a three-dimensional silicon-carbon negative electrode material on the surface of spherical silicon powder, and realizes the orderly growth of carbon nanotubes through a composite activator system and a multi-stage heat treatment process. The obtained composite material has a unique three-dimensional network structure and exhibits excellent structural stability.
[0011] In order to achieve the above objectives, on the one hand, the present invention provides a method for preparing a carbon nanotube / silicon three-dimensional composite material, wherein the preparation method comprises:
[0012] Step (1) composite activation of silicon powder surface: spherical silicon powder is dispersed in a solution containing an alkaline activator at a mass ratio of 1:15-1:60, and then a zwitterionic surfactant solution and a silane coupling agent are added in sequence and ultrasonic treatment is performed to obtain active spherical silicon powder with an ordered molecular assembly layer on the surface, i.e., activated spherical silicon powder;
[0013] Wherein, in the solution containing the alkaline activator, the concentration of the alkaline activator is 0.3-2.5 mol / L;
[0014] Step (2) constructing a core-shell structured nanocatalyst: dispersing active spherical silicon powder in an alcohol solution of a transition metal salt and a rare earth metal salt at a molar ratio of active spherical silicon powder to transition metal (i.e., a molar ratio of silicon in the active spherical silicon powder to transition metal) of 1:0.05-1:0.4 and a molar ratio of transition metal to rare earth metal of 1:0.02-1:0.2, and then heat-treating the resulting mixed solution using a three-stage heat treatment process to load the core-shell structured nanocatalyst on the surface of the active spherical silicon powder; wherein the temperature of the third stage heat treatment process in the three-stage heat treatment process is 480-620° C.;
[0015] Step (3) radial growth of carbon nanotubes: placing the product obtained in step (2) in a tubular furnace, introducing an inert gas and a carbon source gas into the tubular furnace by pulsed atmosphere switching, and then introducing an oxygen-containing organic matter to react, so as to achieve radial arrangement and growth of the carbon nanotubes, thereby obtaining the carbon nanotube / silicon three-dimensional composite material;
[0016] The volume ratio of the inert gas to the carbon source gas is 0.5:1-3:1, and the volume ratio of the oxygen-containing organic matter to the carbon source gas is 0.002:1-0.015:1.
[0017] As a specific embodiment of the preparation method described above of the present invention, in step (1), the solution containing the alkaline activator includes one or a combination of sodium carbonate solution, sodium bicarbonate solution, potassium carbonate solution, potassium bicarbonate solution, ammonium bicarbonate solution, sodium hydroxide solution, potassium hydroxide solution and ammonia solution.
[0018] As a specific embodiment of the above preparation method of the present invention, in step (1), the pH value of the solution containing the alkaline activator is 9-12.
[0019] As a specific embodiment of the preparation method described above of the present invention, in step (1), the mass ratio of the zwitterionic surfactant solution to the spherical silicon powder is 1:10-1:50, and the mass fraction of the zwitterionic surfactant in the zwitterionic surfactant solution is 0.05-1.0wt%.
[0020] As a specific embodiment of the preparation method described above of the present invention, in step (1), the zwitterionic surfactant includes one or a combination of several of the following: Zonyl FS series zwitterionic surfactants, alkyl sulfonyl betaine with a carbon chain length of C8-C16, and alkyl dimethyl betaine with a carbon chain length of C8-C16.
[0021] As a specific embodiment of the preparation method described above of the present invention, in step (1), the Zonyl FS series zwitterionic surfactant includes one or a combination of FS-300, FS-500 and FS-610.
[0022] As a specific embodiment of the preparation method described above of the present invention, in step (1), the silane coupling agent includes one or a combination of KH-550 (γ-aminopropyltriethoxysilane), KH-560 (γ-glycidyl ether propyltrimethoxysilane), KH-590 (γ-mercaptopropyltrimethoxysilane), KH-570 (γ-methacryloxypropyltrimethoxysilane) and KH-792 (N-β-aminoethyl-γ-aminopropyltrimethoxysilane).
[0023] As a specific embodiment of the preparation method described above, in step (1), based on the total weight of the spherical silicon powder being 100%, the amount of the silane coupling agent used is 0.3-3.0 wt%.
[0024] As a specific embodiment of the above-mentioned preparation method of the present invention, in step (1), the average particle size of the spherical silicon powder is 20-150 nm.
[0025] As a specific embodiment of the above preparation method of the present invention, in step (1), the ultrasonic treatment is ultrasonic treatment at 35-65° C. for 20-70 min.
[0026] In step (1) of the preparation method described above, the dispersion can be achieved by stirring. As a specific embodiment of the preparation method described above, in step (1), the spherical silicon powder is dispersed in a solution containing an alkaline activator at a mass ratio of 1:15-1:60, stirred at a speed of 4000-9000 r / min for 10-30 min, then a zwitterionic surfactant solution is added, stirring is continued for 5-25 min, a silane coupling agent is continued to be added and ultrasonic treatment is performed to obtain an active spherical silicon powder having an ordered molecular assembly layer on the surface, i.e., activated spherical silicon powder.
[0027] The preparation method of the carbon nanotube / silicon three-dimensional composite material provided by the present invention first uses an alkaline activator and a zwitterionic surfactant compound system to modify the surface of spherical silicon powder, and introduces a zwitterionic surfactant and a silane coupling agent to form an ordered molecular assembly layer to achieve coordinated regulation of the surface chemical state and active site density. The formation mechanism of the ordered molecular assembly layer is as follows:
[0028] First, the alkaline activator reacts with the Si-O-Si bonds on the surface of the spherical silicon powder to generate Si-OH active groups;
[0029] The zwitterionic surfactant molecules physically adsorb to the surface Si-OH active groups through their hydrophilic groups and are arranged in an orderly manner through the van der Waals force between their hydrophobic groups to form an initial molecular layer;
[0030] The alkoxy groups (-OR) in the silane coupling agent molecules react with the surface Si-OH active groups to form a covalently bonded Si-O-Si network structure. At the same time, other functional groups (such as -NH2, -SH, etc.) in the silane coupling agent molecules form a stable composite interface layer with zwitterionic surfactants through electrostatic and hydrogen bonding. This orderly arranged composite molecular layer not only provides uniformly distributed functional groups, but also forms a surface structure with a specific orientation, which provides a basis for the subsequent directional loading of core-shell structured nanocatalysts.
[0031] As a specific embodiment of the preparation method described above of the present invention, in step (2), the transition metal salt includes one or a combination of transition metal nitrates, acetates, chlorides and sulfates, and the rare earth metal salt includes one or a combination of rare earth metal nitrates, acetates, chlorides and sulfates.
[0032] As a specific embodiment of the preparation method described above of the present invention, in step (2), the transition metal includes one or a combination of Ni, Fe, Co, Cu and Mn, and the rare earth metal includes one or a combination of La, Ce, Y, Nd and Pr.
[0033] As a specific embodiment of the preparation method described above of the present invention, in step (2), the alcohol used in the alcohol solution of the transition metal salt and the rare earth metal salt includes one or a combination of methanol, ethanol, n-propanol, isopropanol and glycerol.
[0034] As a specific embodiment of the preparation method described above, in step (2), the three-stage heat treatment process specifically includes:
[0035] The first stage of heat treatment process is to keep the temperature at 180-320℃ for 0.5-2.5h in an inert atmosphere to pretreat the mixed liquid;
[0036] The second stage heat treatment process is to keep the temperature at 330-470℃ for 1.5-4.5h in air atmosphere to achieve the transformation of hydroxide into metal oxide;
[0037] The third stage heat treatment process is to keep the temperature at 480-620°C for 0.3-2.5h in a mixed atmosphere of water vapor and hydrogen to achieve the transformation of the metal oxide into a core-shell structured nanocatalyst.
[0038] As a specific embodiment of the preparation method described above, in step (2), the inert atmosphere (carrier gas) used in the first stage heat treatment process includes one or a combination of nitrogen, argon and helium.
[0039] As a specific embodiment of the preparation method described above, in step (2), in the third stage heat treatment process, the volume content of water vapor is 2-8 vol%, based on the total volume of the mixed atmosphere being 100%.
[0040] As a specific embodiment of the preparation method described above of the present invention, in step (2), the size of the core-shell structured nanocatalyst is 3-8 nm.
[0041] In the present invention, the core-shell structure nanocatalyst has a metal element as the core, and the core is coated with a shell. The metal element as the core is a reduced transition metal (such as one or a combination of Ni, Fe, Co, Cu and Mn), and the shell is a nanostructure of a rare earth metal oxide, and the nanostructure of the rare earth metal oxide includes a rare earth metal oxide formed by a rare earth metal of one or a combination of La, Ce, Y, Nd and Pr (such as La2O3, CeO2, etc.). In step (2) of the preparation method described above, the core-shell structure nanocatalyst with a special structure is loaded on the surface of the active spherical silicon powder, which is beneficial to improve the catalytic activity and stability of the catalyst, and further beneficial to the radial growth of carbon nanotubes. In addition, the design of this core-shell structure nanocatalyst is completely different from the traditional single metal catalytic system. The present invention significantly improves the selectivity of carbon nanotube growth through the electronic structure regulation of the core-shell structure nanocatalyst, and solves the key problems of random growth orientation and poor structural uniformity of carbon nanotubes in the prior art. Hereinafter, the applicant will explain the electronic structure regulation function of the nanocatalyst doped with rare earth and transition metal and having a special core-shell structure used in the present invention from the aspects of the basis of electronic structure regulation, the regulation process and the regulation effect.
[0042] The basis of electronic structure regulation:
[0043] In the nanocatalyst with a special core-shell structure used in the present invention, the core formed by the transition metal provides d orbital electrons, and these incompletely filled d orbitals are active centers for carbon source decomposition and carbon atom recombination, while the nanostructured shell of the rare earth metal oxide has a special 4f electronic configuration, and the electron density can be adjusted through oxygen vacancies.
[0044] Regulation process:
[0045] During use, the nanostructured shell of the rare earth metal oxide in the catalyst changes the electronic state of the core formed by the transition metal through the interface effect, and the strong electric field effect of the rare earth ions affects the energy level distribution of the transition metal d orbital electrons, and the oxygen vacancies in the nanostructured shell of the rare earth metal oxide promote the transfer and redistribution of electrons at the interface between the transition metal (core) and the rare earth metal oxide (shell).
[0046] Control effect:
[0047] The d-orbital electron density of the transition metal is optimized, which improves the catalytic decomposition activity of the catalyst for carbon sources. The unique electronic structure formed at the interface between the transition metal (core) and the rare earth metal oxide (shell) is conducive to the directional diffusion of carbon atoms, and the electronic regulation effect of the nanostructured shell of the rare earth metal oxide can also inhibit the disordered growth of carbon nanotubes.
[0048] As a specific embodiment of the preparation method described above of the present invention, in step (2), the heating rates in the first stage heat treatment process, the second stage heat treatment process and the third stage heat treatment process are 2-10°C / min, 3-15°C / min and 5-20°C / min respectively.
[0049] As a specific embodiment of the preparation method described above of the present invention, in step (3), the carbon source gas includes one or a combination of methane, ethylene, acetylene and propylene.
[0050] As a specific embodiment of the preparation method described above of the present invention, in step (3), the inert gas (carrier gas) includes one or a combination of nitrogen, argon and helium.
[0051] As a specific embodiment of the preparation method described above, in step (3), the oxygen-containing organic matter includes one or a combination of alcohols, ketones, and ethers. The oxygen-containing organic matter is used as a growth regulator, and the mechanism of the oxygen-containing organic matter being used as a growth regulator is as follows:
[0052] The oxygen-containing organic matter used in the present invention undergoes partial thermal decomposition at high temperature to produce active oxygen-containing species (such as -OH, -O-, etc.). These active oxygen-containing species can selectively etch the amorphous carbon on the catalyst surface, maintain the accessibility of the catalyst active sites, and regulate the supply rate of carbon atoms during the growth of carbon nanotubes, thereby avoiding non-directional growth caused by supersaturation of the carbon source.
[0053] As a specific embodiment of the preparation method described above of the present invention, in step (3), the alcohol substance includes one or a combination of methanol, ethanol and isopropanol, the ketone substance includes acetone and / or methyl ethyl ketone, and the ether substance includes tetrahydrofuran and / or ethyl ether.
[0054] As a specific embodiment of the preparation method described above of the present invention, in step (3), the reaction is carried out at a temperature of 550-900° C. and a pressure of 0.3-3 MPa for 10-50 min.
[0055] As a specific embodiment of the preparation method described above, in step (3), the cycle of the pulsed atmosphere switching mode is: inert gas is introduced for 15-35 seconds, and carbon source gas is introduced for 15-35 seconds.
[0056] The preparation method of the carbon nanotube / silicon three-dimensional composite material provided by the present invention first uses an alkaline activator and a zwitterionic surfactant compounding system to modify the surface of spherical silicon powder, and forms an ordered molecular assembly layer by introducing a zwitterionic surfactant and a silane coupling agent to achieve coordinated regulation of the surface chemical state and the density of active sites; then the surface ordered molecular assembly layer is used to coordinate with a metal salt precursor containing a transition metal element and a metal salt precursor containing a rare earth element, and an ordered catalytic site is constructed at the spherical interface; then, through a precisely controlled segmented heat treatment process, a nanocatalytic center with a core-shell structure is constructed under the alternating action of an oxidation-reduction atmosphere, and finally, under the conditions of regulating the reaction pressure and the atmosphere components, the controllable growth of carbon nanotubes on the surface of spherical silicon powder is achieved. For example, in one embodiment of the present invention, a ZonylFS-300 zwitterionic surfactant and a KH-550 silane coupling agent are compounded and combined with a rare earth-doped nickel salt (Ni-La) catalyst system, so that carbon nanotubes form a unique radially arranged three-dimensional network structure on the surface of spherical silicon powder, showing excellent structural stability.
[0057] On the other hand, the present invention also provides a carbon nanotube / silicon three-dimensional composite material, wherein the carbon nanotube / silicon three-dimensional composite material is prepared by the preparation method of the carbon nanotube / silicon three-dimensional composite material described above, and presents a three-dimensional network composite structure, including spherical silicon powder and carbon nanotubes radially arranged and grown on the surface of the spherical silicon powder.
[0058] As a specific embodiment of the carbon nanotube / silicon three-dimensional composite material described above in the present invention, the structural parameters of the carbon nanotubes include: tube diameter (average diameter) of 15-60 nm and tube length of 0.3-3 μm.
[0059] In yet another aspect, the present invention further provides the use of the above-mentioned carbon nanotube / silicon three-dimensional composite material in lithium-ion battery negative electrode materials, energy storage devices, catalyst carriers or thermal management materials.
[0060] Compared with the prior art, the technical solution provided by the present invention can achieve the following beneficial technical effects:
[0061] In the prior art, the preparation of carbon / silicon composite materials mainly relies on simple physical mixing or surface carbon coating, but these methods are difficult to effectively control the interface structure and carbon layer distribution. The present invention creatively designs a synergistic activation system of alkaline activators and zwitterionic surfactants, and constructs an interfacial active layer with regular orientation, i.e., an ordered molecular assembly layer, on the surface of spherical silicon powder through a precisely controlled molecular self-assembly process. The ordered molecular assembly layer constructed on the surface of spherical silicon powder by this unique interface molecular engineering method not only ensures the uniform distribution of catalytic centers, but also lays the foundation for the subsequent directional growth of carbon nanotubes.
[0062] In terms of catalyst design, the present invention has made a breakthrough in proposing the core-shell structure concept of rare earth-doped transition metal catalysts. Through an innovative three-stage heat treatment process, precise control of the size and distribution of catalytic active centers is achieved. This design is completely different from the traditional single metal catalytic system. Through the electronic structure regulation of the core-shell structure nanocatalyst, the selectivity of carbon nanotube growth is significantly improved, solving the key problems of random growth orientation and poor structural uniformity of carbon nanotubes in the prior art.
[0063] It is particularly worth emphasizing that the present invention uses pulsed atmosphere switching technology for the first time to regulate the growth dynamics of carbon nanotubes. This innovative growth strategy establishes a dynamic balance between carbon source supply and surface diffusion, and successfully achieves radial arrangement and growth of carbon nanotubes on the surface of spherical silicon powder through the coordinated optimization of reaction temperature, reaction pressure and atmosphere components (including carrier gas, carbon source gas and oxygen-containing organic matter). Compared with the traditional continuous vapor deposition process, the preparation method provided by the present invention not only simplifies the process flow, but more importantly, constructs a unique three-dimensional conductive network structure, providing an efficient channel for electron transmission. At the same time, the carbon nanotube / silicon three-dimensional composite material also exhibits excellent structural stability.
[0064] The innovation of the present invention is directly reflected in the significant improvement in the performance of the carbon nanotube / silicon three-dimensional composite material. In one embodiment of the present invention, through multi-scale structural design and process parameter optimization, the prepared carbon nanotube / silicon three-dimensional composite material exhibits excellent performance as a negative electrode material for lithium-ion batteries, with an initial discharge capacity of 3150mAh / g and a capacity retention rate of 77.1% after 200 cycles. These indicators are at the international leading level. At the same time, thanks to the unique structural design, the carbon nanotube / silicon three-dimensional composite material also exhibits excellent rate performance and interface stability, effectively solving the key scientific problems faced by silicon-based negative electrode materials.
[0065] In terms of practical application, the raw materials used in the present invention are widely available, the process route is simple and controllable, and it has significant cost advantages and large-scale production potential. The overall preparation process is carried out under mild conditions, with low energy consumption, stable product performance, and good batch consistency. These characteristics make the present invention not only of important academic value, but also of practical industrialization prospects, and provide an innovative technical solution for the development of a new generation of high-performance lithium-ion battery negative electrode materials.
[0066] In summary, the present invention has innovatively proposed a novel preparation method for carbon nanotube / silicon three-dimensional composite materials based on molecular self-assembly and directional growth by deeply understanding the principles of interface engineering and catalytic chemistry. Compared with the prior art, the present invention has achieved important breakthroughs in interface regulation, catalytic system design and growth kinetics, and provides an innovative solution for the construction of high-performance silicon-based negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0068] Figure 1 This is a scanning electron microscope image of the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention.
[0069] Figure 2 This is a Raman spectrum of the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention.
[0070] Figure 3 This is a transmission electron microscope image of the carbon nanotube / silicon three-dimensional composite material provided in Example 2 of the present invention.
[0071] Figure 4 This is a cycle performance diagram of the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention.
[0072] Figure 5 This is the first charge and discharge curve of the carbon nanotube / silicon three-dimensional composite material provided in Example 2 of the present invention.
[0073] Figure 6 This is a scanning electron microscope image of the material provided for Comparative Example 1.
[0074] Figure 7 This is a cycle performance diagram of the material provided for Comparative Example 1.
[0075] Figure 8 This is a scanning electron microscope image of the composite material provided for Comparative Example 2. DETAILED DESCRIPTION
[0076] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0077] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values listed are 1 and 2, and the maximum range values listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0078] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.
[0079] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.
[0080] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.
[0081] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0082] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0083] Example 1
[0084] This embodiment provides a carbon nanotube / silicon three-dimensional composite material, which is prepared by a preparation method comprising the following specific steps:
[0085] Step (1) Surface composite activation of silicon powder: Spherical silicon powder with an average particle size of 50 nm is selected and dispersed in a sodium carbonate solution with a concentration of 1.5 mol / L at a mass ratio of 1:30, and stirred at a speed of 6000 r / min for 20 minutes. Subsequently, a Zonyl FS-300 zwitterionic surfactant solution with a concentration of 0.5wt% is added, and the mass ratio of the Zonyl FS-300 zwitterionic surfactant solution to the spherical silicon powder is 1:30, and stirring is continued for 15 minutes. Then, a KH-550 silane coupling agent accounting for 1.5wt% of the total weight of the spherical silicon powder is added, and ultrasonic treatment is performed at 50°C for 45 minutes to obtain surface-modified active spherical silicon powder, that is, active spherical silicon powder with an ordered molecular assembly layer on the surface, that is, activated spherical silicon powder.
[0086] Step (2) constructing a core-shell structured nanocatalyst: dispersing the activated spherical silicon powder in an ethanol solution of nickel nitrate with a Si:Ni molar ratio of 1:0.2, and then adding a measured amount of lanthanum nitrate to make a Ni:La molar ratio of 1:0.1 to obtain a mixed solution. The mixed liquid is treated by a three-stage programmed temperature heating process: first, the mixed liquid is pretreated by heating to 250°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept warm for 1.5 hours; then, the mixed liquid is switched to an air atmosphere and heated to 400°C at a heating rate of 8°C / min and kept warm for 3 hours to achieve the transformation of hydroxide into metal oxide; finally, the mixed liquid is heated to 550°C at a heating rate of 12°C / min in a hydrogen atmosphere containing 5 vol% water vapor and kept warm for 1.5 hours to achieve the transformation of metal oxide into core-shell structured nanocatalyst, thereby achieving the loading of core-shell structured nanocatalyst on the surface of active spherical silicon powder, and the average size of the obtained core-shell structured nanocatalyst is 5.2nm, wherein more than 90% of the catalyst particle sizes are distributed in the range of 4.5-6.0nm.
[0087] Step (3) radial growth of carbon nanotubes: the product obtained in step (2) is placed in a tubular furnace, and nitrogen and ethylene are introduced into the tubular furnace by pulsed atmosphere switching, wherein nitrogen is introduced for 20 seconds and ethylene is introduced for 15 seconds, and the volume ratio of ethylene to nitrogen is controlled to be 1:1, and isopropanol (the volume ratio of isopropanol to ethylene is 0.008:1) is introduced as a growth regulator, and then the reaction is carried out at a temperature of 750°C and a pressure of 1 MPa for 30 minutes to achieve radial arrangement growth of carbon nanotubes, thereby obtaining the carbon nanotube / silicon three-dimensional composite material.
[0088] Example 2
[0089] This embodiment provides a carbon nanotube / silicon three-dimensional composite material, which is prepared by a preparation method comprising the following specific steps:
[0090] Step (1) Surface composite activation of silicon powder: Spherical silicon powder with an average particle size of 40 nm is selected and dispersed in a sodium carbonate solution with a concentration of 1.5 mol / L at a mass ratio of 1:30, and stirred at a speed of 6000 r / min for 20 min. Subsequently, a Zonyl FS-300 zwitterionic surfactant solution with a concentration of 0.5 wt% is added, and the mass ratio of the Zonyl FS-300 zwitterionic surfactant solution to the spherical silicon powder is 1:30, and stirring is continued for 15 min. Then, a KH-550 silane coupling agent accounting for 1.5 wt% of the total weight of the spherical silicon powder is added, and ultrasonic treatment is performed at 50° C. for 45 min to obtain surface-modified active spherical silicon powder, that is, active spherical silicon powder with an ordered molecular assembly layer on the surface, that is, activated spherical silicon powder.
[0091] Step (2) constructing a core-shell structured nanocatalyst: dispersing the activated spherical silicon powder in an ethanol solution of ferric nitrate with a Si:Fe molar ratio of 1:0.2, and then adding a measured amount of cerium sulfate to make a Fe:Ce molar ratio of 1:0.15 to obtain a mixed solution. The mixed liquid is treated by a three-stage programmed temperature heating process: first, the mixed liquid is pretreated by heating to 250°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 1.5 hours; then, the mixed liquid is switched to an air atmosphere and heated to 400°C at a heating rate of 8°C / min and kept warm for 3 hours to achieve the transformation of hydroxide into metal oxide; finally, the mixed liquid is heated to 550°C at a heating rate of 12°C / min under a hydrogen atmosphere containing 5 vol% water vapor and kept warm for 1.5 hours to achieve the transformation of metal oxide into core-shell structured nanocatalyst, thereby achieving the loading of core-shell structured nanocatalyst on the surface of active spherical silicon powder, and the average size of the obtained core-shell structured nanocatalyst is 4.8nm, and the size distribution range is 4.0-5.5nm.
[0092] Step (3) radial growth of carbon nanotubes: the product obtained in step (2) is placed in a tubular furnace, and nitrogen and propylene are introduced into the tubular furnace by pulsed atmosphere switching, wherein nitrogen is introduced for 15 seconds and propylene is introduced for 15 seconds, and the volume ratio of propylene to nitrogen is controlled to be 1:1, and then isopropanol (the volume ratio of isopropanol to propylene is 0.008:1) is introduced as a growth regulator, and the reaction is carried out at a temperature of 630°C and a pressure of 1 MPa for 30 minutes to achieve radial arrangement growth of carbon nanotubes, thereby obtaining the carbon nanotube / silicon three-dimensional composite material.
[0093] Example 3
[0094] This embodiment provides a carbon nanotube / silicon three-dimensional composite material, which is prepared by a preparation method comprising the following specific steps:
[0095] Step (1) Surface composite activation of silicon powder: Spherical silicon powder with an average particle size of 80 nm is selected and dispersed in a sodium bicarbonate solution with a concentration of 2.0 mol / L at a mass ratio of 1:40, and stirred at a speed of 7500 r / min for 20 min. Subsequently, a Zonyl FS-300 zwitterionic surfactant solution with a concentration of 0.5 wt% is added, and the mass ratio of the Zonyl FS-300 zwitterionic surfactant solution to the spherical silicon powder is 1:30, and stirring is continued for 15 min. Then, a KH-550 silane coupling agent accounting for 2.0 wt% of the total weight of the spherical silicon powder is added, and ultrasonic treatment is performed at 50° C. for 45 min to obtain surface-modified spherical active silicon powder, that is, active spherical silicon powder with an ordered molecular assembly layer on the surface, that is, activated spherical silicon powder.
[0096] Step (2) constructing a core-shell structured nanocatalyst: dispersing the activated spherical silicon powder in an ethanol solution of cobalt nitrate with a Si:Co molar ratio of 1:0.25, and then adding a measured amount of yttrium chloride to make a Co:Y molar ratio of 1:0.08 to obtain a mixed solution. The mixed liquid is treated by a three-stage programmed temperature heating process: first, the mixed liquid is pretreated by heating to 280°C at a heating rate of 4°C / min in a helium atmosphere and kept warm for 2 hours; then, the mixed liquid is switched to an air atmosphere and heated to 420°C at a heating rate of 10°C / min and kept warm for 4 hours to achieve the transformation of hydroxide into metal oxide; finally, the mixed liquid is heated to 580°C at a heating rate of 15°C / min and kept warm for 2 hours in a hydrogen atmosphere containing 6.5 vol% water vapor to achieve the transformation of metal oxide into a core-shell structured nanocatalyst, thereby achieving the loading of the core-shell structured nanocatalyst on the surface of the active spherical silicon powder. The average size of the obtained core-shell structured nanocatalyst is 6.5 nm, and more than 90% of the catalyst particles are distributed in the range of 5.8-7.2 nm.
[0097] Step (3) radial growth of carbon nanotubes: the product obtained in step (2) is placed in a tubular furnace, and helium and methane are introduced into the tubular furnace by pulsed atmosphere switching, wherein helium is introduced for 15 seconds and methane is introduced for 25 seconds, and the volume ratio of methane to helium is controlled to be 1:1.5, and then tetrahydrofuran (the volume ratio of tetrahydrofuran to methane is 0.01:1) is introduced as a growth regulator, and the reaction is carried out at a temperature of 900°C and a pressure of 1 MPa for 40 minutes to achieve radial arrangement and growth of carbon nanotubes, thereby obtaining the carbon nanotube / silicon three-dimensional composite material.
[0098] Example 4
[0099] This embodiment provides a carbon nanotube / silicon three-dimensional composite material, which is prepared by a preparation method comprising the following specific steps:
[0100] Step (1) Surface composite activation of silicon powder: Spherical silicon powder with an average particle size of 100 nm is selected and dispersed in an ammonia solution with a concentration of 1.8 mol / L at a mass ratio of 1:50, and stirred at a speed of 8000 r / min for 25 minutes. Subsequently, a 1.0 wt% Zonyl FS-610 zwitterionic surfactant solution is added, and the mass ratio of the Zonyl FS-610 zwitterionic surfactant solution to the silicon powder is 1:30, and stirring is continued for 20 minutes. Then, 0.5 wt% of the total weight of the spherical silicon powder is added with a KH-792 silane coupling agent, and ultrasonic treatment is performed at 60° C. for 55 minutes to obtain surface-modified active spherical silicon powder, that is, active spherical silicon powder with an ordered molecular assembly layer on the surface, that is, activated spherical silicon powder.
[0101] Step (2) constructing a core-shell structured nanocatalyst: dispersing the activated spherical silicon powder in anhydrous ethanol, adding nickel nitrate, iron nitrate and lanthanum nitrate in calculated amounts in sequence, so that the molar ratio of Si: (Ni + Fe) is 1:0.3, wherein the molar ratio of Ni:Fe:La is 0.6:0.4:0.1, to obtain a mixed solution. The mixed liquid is treated by a three-stage programmed temperature heating process: first, the mixed liquid is pretreated by heating to 300°C at a heating rate of 3°C / min under an argon atmosphere and kept warm for 2.2 hours; then, the mixed liquid is switched to an air atmosphere and heated to 450°C at a heating rate of 12°C / min and kept warm for 4.5 hours to achieve the transformation of hydroxide into metal oxide; finally, the mixed liquid is heated to 600°C at a heating rate of 18°C / min and kept warm for 1.8 hours under a hydrogen atmosphere containing 7.0 vol% water vapor to achieve the transformation of metal oxide into core-shell structured nanocatalyst, thereby achieving the loading of core-shell structured nanocatalyst on the surface of active spherical silicon powder, and the average size of the obtained core-shell structured nanocatalyst is 5.8 nm, and the size distribution range is 5.0-6.5 nm.
[0102] Step (3) radial growth of carbon nanotubes: placing the product obtained in step (2) in a tubular furnace, introducing helium and a mixture of ethylene and acetylene into the tubular furnace by pulsed atmosphere switching, wherein helium is introduced for 22 seconds and the mixture of ethylene and acetylene is introduced for 18 seconds, and the volume ratio of the mixture of ethylene and acetylene to helium is controlled to be 1:2, and the volume ratio of ethylene to acetylene in the mixture of ethylene and acetylene is controlled to be 3:1, and then methanol (the volume ratio of methanol to the mixture of ethylene and acetylene is 0.012:1) is introduced as a growth regulator, and the reaction is carried out at a temperature of 750°C and a pressure of 2MPa for 45 minutes to achieve radial arrangement growth of carbon nanotubes, thereby obtaining the carbon nanotube / silicon three-dimensional composite material.
[0103] Example 5
[0104] This embodiment provides a carbon nanotube / silicon three-dimensional composite material, which is prepared by a preparation method comprising the following specific steps:
[0105] Step (1) Surface composite activation of silicon powder: Spherical silicon powder with an average particle size of 35 nm is selected and dispersed in a 1.2 mol / L ammonium bicarbonate solution at a mass ratio of 1:25, and stirred at a speed of 5500 r / min for 15 min. Subsequently, a zwitterionic surfactant solution mixed with 0.3 wt% Zonyl FS-300 and 0.2 wt% C12 alkyl sulfobetaine is added, and the mass ratio of the mixed zwitterionic surfactant solution to the spherical silicon powder is 1:30, and stirring is continued for 18 min. Then, a KH-570 silane coupling agent accounting for 1.8 wt% of the total weight of the spherical silicon powder is added, and ultrasonic treatment is performed at 45° C. for 50 min to obtain surface-modified active spherical silicon powder, that is, active spherical silicon powder with an ordered molecular assembly layer on the surface, that is, activated spherical silicon powder.
[0106] Step (2) constructing a core-shell structured nanocatalyst: dispersing the activated spherical silicon powder in anhydrous ethanol, adding nickel nitrate and cerium nitrate in calculated amounts in sequence to make the molar ratio of Si:Ni be 1:0.15 and the molar ratio of Ni:Ce be 1:0.12, and obtaining a mixed solution. The mixed liquid is treated by a three-stage programmed temperature heating process: first, the mixed liquid is pretreated by heating to 220°C at a heating rate of 4.5°C / min in a nitrogen atmosphere and kept warm for 1.8 hours; then, the mixed liquid is switched to an air atmosphere and heated to 380°C at a heating rate of 9°C / min and kept warm for 3.8 hours to achieve the transformation of hydroxide into metal oxide; finally, the mixed liquid is heated to 520°C at a heating rate of 16°C / min in a hydrogen atmosphere containing 4.5 vol% water vapor and kept warm for 1.2 hours to achieve the transformation of metal oxide into core-shell structured nanocatalyst, thereby achieving the loading of core-shell structured nanocatalyst on the surface of active spherical silicon powder, and the average size of the obtained core-shell structured nanocatalyst is 4.5 nm, wherein more than 85% of the catalyst particles are distributed in the range of 4.0-5.0 nm.
[0107] Step (3) radial growth of carbon nanotubes: the product obtained in step (2) is placed in a tubular furnace, and nitrogen and ethylene are introduced into the tubular furnace by pulsed atmosphere switching, wherein nitrogen is introduced for 35 seconds and ethylene is introduced for 20 seconds, and the volume ratio of ethylene to nitrogen is controlled to be 1:1.2, and then isopropanol (the volume ratio of isopropanol to ethylene is 0.006:1) is introduced as a growth regulator, and the reaction is carried out at a temperature of 780°C and a pressure of 2.5 MPa for 35 minutes to achieve radial arrangement and growth of carbon nanotubes, thereby obtaining the carbon nanotube / silicon three-dimensional composite material.
[0108] Comparative Example 1
[0109] The difference between this comparative example and Example 1 is only that: the concentration of sodium carbonate solution is 3.5 mol / L.
[0110] Comparative Example 2
[0111] The difference between this comparative example and Example 1 is that the temperature of the third stage heat treatment process in the three-stage heat treatment process in step (2) is 680°C.
[0112] Comparative Example 3
[0113] This comparative example adopts the same conditions as Example 1, except that: the step of adding the zwitterionic surfactant solution and the silane coupling agent is omitted, and the catalyst loading is directly carried out after alkaline activation with the alkaline activator. Observation of the scanning electron microscope image of the intermediate product obtained in this comparative example shows that the catalyst is unevenly distributed on the surface of the spherical silicon powder and is severely agglomerated, which is caused by the lack of regulation of the ordered molecular assembly layer. In addition, the carbon nanotubes in the final composite material are disordered. The capacity retention rate of the final composite material obtained in this comparative example after 200 cycles at a current density of 1A / g is measured by a charge and discharge tester. It is only 48%, indicating that its performance is significantly worse than the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention.
[0114] Comparative Example 4
[0115] This comparative example adopts the same conditions as Example 1, except that no sodium carbonate solution is added for alkaline activation. At this time, due to the lack of sufficient active sites on the surface of the spherical silicon powder, it is difficult for the zwitterionic surfactant and the silane coupling agent to form a stable molecular assembly layer. Transmission electron microscopy observation shows that the catalyst loading is low and unevenly distributed, and the carbon nanotubes grow sparsely. The electrochemical performance test using a charge and discharge tester shows that the first cycle discharge capacity of the composite material obtained in this comparative example at a current of 0.1A / g is only 1800mAh / g, indicating that its performance is also significantly worse than the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention.
[0116] Comparative Example 5
[0117] This comparative example adopts the same conditions as Example 1, except that the three-stage heat treatment in step (2) is simplified to a single-stage heat treatment, that is, directly heat-treated at 550°C for 2h in a hydrogen atmosphere. The experimental results show that due to the lack of the alternating effect of the redox atmosphere, the nanocatalyst cannot form an ideal core-shell structure, and the catalyst particle size distribution range is expanded to 2-15nm. At the same time, the cycle stability of the composite material finally obtained in this comparative example is significantly reduced. The capacity decay of the composite material after 100 cycles at a current density of 1A / g is more than 40%, indicating that its performance is also significantly worse than the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention.
[0118] Comparative Example 6
[0119] This comparative example adopts the same conditions as Example 1, except that no isopropanol is added during the radial growth of carbon nanotubes in step (3). The results show that the growth rate of carbon nanotubes is out of control, and a large amount of amorphous carbon deposits appear on the surface, resulting in catalyst deactivation. Raman spectroscopy shows that D / I G The ratio increased to 0.85, indicating that the degree of graphitization was significantly reduced.
[0120] Comparative Example 7
[0121] This comparative example adopts the same conditions as Example 1, except that: instead of using a pulsed atmosphere switching method to introduce nitrogen and ethylene into the tube furnace, a continuous introduction method is used, that is, nitrogen and ethylene are introduced simultaneously, and the volume ratio of the two is still 1:1. Scanning electron microscopy observation shows that due to the lack of dynamic regulation of pulsed atmosphere switching, the growth orientation of carbon nanotubes is random, the tube diameter distribution is uneven (15-100nm), and it is difficult for carbon nanotubes to form an ideal radial arrangement structure.
[0122] Comparative Example 8
[0123] This comparative example adopts the same conditions as Example 1, except that the reaction pressure during the radial growth of carbon nanotubes in step (3) is reduced to 0.1 MPa, and the volume ratio of ethylene to nitrogen is adjusted to 5:1. The results show that under low pressure and high carbon source concentration, although carbon nanotubes can grow rapidly, their orientation is disordered and they cannot form an ordered three-dimensional network structure. The cycle performance test results show that the capacity retention rate of the composite material finally obtained in this comparative example after 200 cycles at a current density of 1 A / g is only 45%, indicating that its performance is also significantly worse than the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention.
[0124] Test Example 1
[0125] In this test example, scanning electron microscope analysis was performed on the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention, the material provided in Comparative Example 1, and the composite material provided in Comparative Example 2. The obtained scanning electron microscope images are as follows: Figure 1 , Figure 6 and Figure 8 shown.
[0126] in, Figure 1 The scanning electron microscope image of the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention shows that the carbon nanotube / silicon three-dimensional composite material presents a unique three-dimensional network composite structure, and radially arranged carbon nanotubes are successfully grown on the surface of spherical silicon powder. The tube length is about 1 μm and the average diameter is 20 nm.
[0127] Figure 6 The scanning electron microscope image of the material provided for Comparative Example 1 shows that no carbon nanotubes are generated in the product obtained in Comparative Example 1, indicating that the excessively high concentration of the alkaline activator causes excessive corrosion on the surface of the spherical silicon powder, forming a large amount of silicon oxide, which seriously affects the subsequent bonding of the zwitterionic surfactant and the silane coupling agent, thereby causing the catalyst to be unable to be deposited on the surface of the spherical silicon powder, thereby causing the inability to grow carbon tubes and construct a three-dimensional composite structure.
[0128] Figure 8 The scanning electron microscope image of the composite material provided in Comparative Example 2 shows that the core-shell structure of the catalyst in the composite material provided in Comparative Example 2 is destroyed, and the rare earth oxide phase is partially decomposed. This change directly affects the growth behavior of carbon nanotubes, resulting in disordered growth orientation and uneven tube diameter distribution (20-150nm). More importantly, the radial arrangement characteristics of carbon nanotubes disappear, and the expected three-dimensional conductive network structure cannot be formed. The fundamental reason for this phenomenon is that the temperature of the third stage heat treatment process in the three-stage heat treatment process of step (2) of Comparative Example 2 is too high, reaching 680°C. The excessively high heat treatment temperature causes the catalyst particles to agglomerate significantly, and the average particle size increases to 15-20nm, far exceeding the ideal range of 3-8nm.
[0129] Test Example 2
[0130] In this test example, Raman spectroscopy analysis was performed on the carbon nanotube / silicon three-dimensional composite materials provided in Examples 1 to 5 of the present invention, wherein the Raman spectrum of the carbon nanotube / silicon three-dimensional composite material of Example 1 is shown in FIG. Figure 2 As shown. Figure 2 It can be seen that at 1350cm -1 and 1580cm -1 The typical D peak and G peak of carbon nanotubes appeared at I D / I G The ratio is 0.24, indicating that the carbon nanotubes have a good degree of graphitization.
[0131] For the carbon nanotube / silicon three-dimensional composite materials provided in Examples 2 to 5, the carbon nanotube / silicon three-dimensional composite materials have a wavelength of 1350 cm -1 and 1580cm -1 The typical D peak and G peak of carbon nanotubes also appear at I D / I G The ratios are 0.21, 0.22, 0.23 and 0.26, respectively, indicating that the carbon nanotubes in these carbon nanotube / silicon three-dimensional composite materials also have a good degree of graphitization.
[0132] Test Example 3
[0133] In this test example, the carbon nanotube / silicon three-dimensional composite material provided in Example 2 of the present invention was analyzed by transmission electron microscopy. The obtained transmission electron microscopy image is as follows Figure 3 As shown. Figure 3 It can be seen that in the carbon nanotube / silicon three-dimensional composite material, carbon nanotubes are entangled at the interface of spherical silicon powder, indicating that there is a good composite state between the spherical silicon powder and the carbon nanotubes.
[0134] Test Example 4
[0135] In this test example, a charge-discharge tester was used to measure the electrode performance of the carbon nanotube / silicon three-dimensional composite materials provided in Examples 1 to 5 of the present invention, the material provided in Comparative Example 1, and the composite material provided in Comparative Example 2. The results are as follows:
[0136] The carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention has a first cycle coulombic efficiency of 91.5% at a current of 0.1 A / g, and an initial discharge capacity of 3150 mAh / g. Figure 4 is a cycle performance diagram of the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention. Figure 4 It can be seen that after 200 cycles at a current density of 1 A / g, the capacity retention rate of the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention is 77.1%, showing good electrochemical performance.
[0137] Figure 5 The first charge-discharge curve of the carbon nanotube / silicon three-dimensional composite material provided in Example 2 of the present invention after the electrode performance is measured by a charge-discharge tester. It can be seen that the first cycle coulomb efficiency of the carbon nanotube / silicon three-dimensional composite material provided in Example 2 of the present invention at a current of 0.1A / g is 91.2%. After 200 cycles at a current density of 1A / g, the capacity retention rate is 72.5%, showing good cycle characteristics.
[0138] The carbon nanotube / silicon three-dimensional composite material provided in Example 3 of the present invention has a first-cycle coulombic efficiency of 91.8% at a current of 0.1 A / g. After 200 cycles at a current density of 1 A / g, the capacity retention rate is 73.8%, showing good cycle characteristics.
[0139] The carbon nanotube / silicon three-dimensional composite material provided in Example 4 of the present invention has a first-cycle coulombic efficiency of 91.6% at a current of 0.1 A / g, and a capacity retention rate of 73.5% after 200 cycles at a current density of 1 A / g, showing good cycle characteristics.
[0140] The carbon nanotube / silicon three-dimensional composite material provided in Example 5 of the present invention has a first-cycle coulombic efficiency of 92.5% at a current of 0.1 A / g, and a capacity retention rate of 73.1% after 200 cycles at a current density of 1 A / g, showing good cycle characteristics.
[0141] The first-cycle coulombic efficiency of the material provided in Comparative Example 1 at a current of 0.1 A / g is only 48%. Figure 7 The cycle performance diagram of the material prepared in this comparative example after the electrode performance was measured by a charge and discharge tester shows that after 50 cycles at a current density of 1A / g, the capacity retention rate is only 42.1%. The performance exhibited is far lower than the cycle performance of the carbon nanotube / silicon three-dimensional composite material provided in Example 1.
[0142] The composite material provided in Comparative Example 2 has an initial discharge capacity of 1350 mAh / g at a current of 0.1 A / g, and a capacity retention rate of only 65% after 100 cycles at a current density of 1 A / g, both of which are far lower than the initial discharge capacity of 3150 mAh / g and the capacity retention rate of 77.1% of the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention. This indicates that the electrical properties and cycle performance of the composite material provided in Comparative Example 2 are significantly worse than those of the carbon nanotube / silicon three-dimensional composite material provided in Example 1 of the present invention.
[0143] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.
Claims
1. A method for preparing a carbon nanotube / silicon three-dimensional composite material, characterized in that: The preparation method comprises: Step (1) composite activation of silicon powder surface: spherical silicon powder is dispersed in a solution containing an alkaline activator at a mass ratio of 1:15-1:60, and then a zwitterionic surfactant solution and a silane coupling agent are added in sequence and ultrasonic treatment is performed to obtain active spherical silicon powder with an ordered molecular assembly layer on the surface; Wherein, in the solution containing the alkaline activator, the concentration of the alkaline activator is 0.3-2.5 mol / L; Step (2) constructing a core-shell structured nanocatalyst: dispersing active spherical silicon powder in an alcohol solution of a transition metal salt and a rare earth metal salt at a molar ratio of 1:0.05-1:0.4 between active spherical silicon powder and transition metal and a molar ratio of 1:0.02-1:0.2 between transition metal and rare earth metal, and then heat-treating the resulting mixed solution using a three-stage heat treatment process to load the core-shell structured nanocatalyst on the surface of the active spherical silicon powder; wherein the temperature of the third stage heat treatment process in the three-stage heat treatment process is 480-620°C; Step (3) radial growth of carbon nanotubes: placing the product obtained in step (2) in a tubular furnace, introducing an inert gas and a carbon source gas into the tubular furnace by pulsed atmosphere switching, and then introducing an oxygen-containing organic matter to react, so as to achieve radial arrangement and growth of the carbon nanotubes, thereby obtaining the carbon nanotube / silicon three-dimensional composite material; The volume ratio of the inert gas to the carbon source gas is 0.5:1-3:1, and the volume ratio of the oxygen-containing organic matter to the carbon source gas is 0.002:1-0.015:
1.
2. The preparation method according to claim 1, characterized in that: In step (1), the solution containing the alkaline activator includes one or a combination of sodium carbonate solution, sodium bicarbonate solution, potassium carbonate solution, potassium bicarbonate solution, ammonium bicarbonate solution, sodium hydroxide solution, potassium hydroxide solution and ammonia solution; Preferably, the pH value of the solution containing the alkaline activator is 9-12.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the mass ratio of the zwitterionic surfactant solution to the spherical silicon powder is 1:10-1:50, and the mass fraction of the zwitterionic surfactant in the zwitterionic surfactant solution is 0.05-1.0wt%; Preferably, the zwitterionic surfactant comprises one or a combination of Zonyl FS series zwitterionic surfactants, alkyl sulfonyl betaine with a carbon chain length of C8-C16, and alkyl dimethyl betaine with a carbon chain length of C8-C16; More preferably, the Zonyl FS series zwitterionic surfactant includes one or a combination of FS-300, FS-500 and FS-610; Also preferably, the silane coupling agent includes one or a combination of KH-550, KH-560, KH-590, KH-570 and KH-792, and even more preferably, based on the total weight of the spherical silicon powder as 100%, the amount of the silane coupling agent is 0.3-3.0wt%; Also preferably, the average particle size of the spherical silicon powder is 20-150 nm; Also preferably, the ultrasonic treatment is carried out at 35-65° C. for 20-70 min.
4. The preparation method according to claim 1, characterized in that: In step (2), the transition metal salt includes one or a combination of transition metal nitrates, acetates, chlorides and sulfates, and the rare earth metal salt includes one or a combination of rare earth metal nitrates, acetates, chlorides and sulfates; Preferably, the transition metal includes one or a combination of Ni, Fe, Co, Cu and Mn, and the rare earth metal includes one or a combination of La, Ce, Y, Nd and Pr.
5. The preparation method according to claim 1 or 4, characterized in that: In step (2), the alcohol used in the alcohol solution of the transition metal salt and the rare earth metal salt includes one or a combination of methanol, ethanol, n-propanol, isopropanol and glycerol.
6. The preparation method according to claim 1 or 4, characterized in that: In step (2), the three-stage heat treatment process specifically includes: The first stage heat treatment process is to keep the temperature at 180-320°C for 0.5-2.5h in an inert atmosphere to pretreat the mixed liquid; preferably, the inert atmosphere includes one or a combination of nitrogen, argon and helium; The second stage heat treatment process is to keep the temperature at 330-470℃ for 1.5-4.5h in air atmosphere to achieve the transformation of hydroxide into metal oxide; The third stage of heat treatment is to keep the temperature at 480-620℃ for 0.3-2.5h in a mixed atmosphere of water vapor and hydrogen to achieve the transformation of metal oxide into core-shell structure nanocatalyst; Also preferably, the volume content of water vapor is 2-8 vol%, based on the total volume of the mixed atmosphere being 100%; Also preferably, the size of the core-shell structured nanocatalyst is 3-8 nm; Also preferably, the heating rates in the first stage heat treatment process, the second stage heat treatment process and the third stage heat treatment process are 2-10°C / min, 3-15°C / min and 5-20°C / min respectively.
7. The preparation method according to claim 1, characterized in that: In step (3), the carbon source gas includes one or a combination of methane, ethylene, acetylene and propylene; Preferably, the inert gas includes one or a combination of nitrogen, argon and helium; Also preferably, the oxygen-containing organic matter includes one or a combination of alcohols, ketones and ethers; More preferably, the alcohol substance includes one or a combination of methanol, ethanol and isopropanol, the ketone substance includes acetone and / or methyl ethyl ketone, and the ether substance includes tetrahydrofuran and / or ethyl ether.
8. The preparation method according to claim 1 or 7, characterized in that: In step (3), the reaction is carried out at a temperature of 550-900° C. and a pressure of 0.3-3 MPa for 10-50 min; Preferably, the cycle of the pulsed atmosphere switching mode is: the inert gas is introduced for 15-35 seconds, and the carbon source gas is introduced for 15-35 seconds.
9. A carbon nanotube / silicon three-dimensional composite material, characterized in that: The carbon nanotube / silicon three-dimensional composite material is prepared by the preparation method of the carbon nanotube / silicon three-dimensional composite material according to any one of claims 1 to 8, and presents a three-dimensional network composite structure, including spherical silicon powder and carbon nanotubes radially arranged and grown on the surface of the spherical silicon powder; Preferably, the structural parameters of the carbon nanotubes include: a tube diameter of 15-60 nm and a tube length of 0.3-3 μm.
10. Use of the carbon nanotube / silicon three-dimensional composite material according to claim 9 in lithium-ion battery negative electrode materials, energy storage devices, catalyst carriers or thermal management materials.
Citation Information
Patent Citations
Preparation of silicon-carbon nanotube composite and product and application thereof
CN109244432A
Preparation method of winding-free carbon nanotube for lithium ion battery
CN111732090A
Modified silicon monoxide / carbon nanotube composite negative electrode material and preparation method thereof
CN112678807A
Carbon nanotube, fluidized bed preparation process thereof and conductive agent
CN115477300A
Rubber composition for a tire comprising a multifunctional polyorganosiloxane as coupling agent
US20030191225A1
Cited By
Mesoporous silicon-carbon composite material with multilevel structure as well as preparation method and application of mesoporous silicon-carbon composite material
CN121317759A